Método para gestão da ocorrência de manifestações patológicas em edificações habitacionais - Milion, Raphael Negri (2019)
Defects are a problem in buildings all over the world. However, there is a shortage of publications that focus on managing this problem. Given that construction companies have limited resources for improvement activities, a method to manage the occurrence of defects is needed. Such a method should be capable of identifying defects that cause the greatest impact on customer satisfaction and finances, in order to focus continuous improvement activities. A method is proposed to manage the occurrence of defects in residential buildings, which is capable of determining the impact of defects on customer satisfaction, as well as their financial impact. The method uses such estimated impacts as inputs to a support decision making tool. Through interviews with companies, the literature review and the investigation of data not previously investigated in the literature, the method determines the impact on customer satisfaction by crossing data from technical assistance departments with data from customer satisfaction surveys, which includes objective questions about the impact of defects on the customer satisfaction. Data on the impact on customer satisfaction, financial impact and the number of occurrences is used as factors in the Choosing by Advantages (CBA) tool, whose output is the choice of the most important defect. Three hypotheses were also tested: H1 - The occurrence of defects in residential buildings negatively impacts customer satisfaction; H2 - Different defects result in different impacts on customer satisfaction and; H3 - The occurrence of defects obtained through interviews with owners or users of residential units is not reliable. The analyzes performed did not confirm H1, whereas H2 and H3 were confirmed. The proposed method was successfully applied to data of a construction company and validated by the company itself. The CBA tool was considered an adequate tool for choosing the most important defect.